Conjugate gradient method for ill – conditioned linear system - Saxena, Vinay; Awasthi, Arun K (International Multidisciplinary Research Journal, 2012)
In this article, an iterative method - Conjugate Gradient Method is used to deal 4 by 4 Wilkinson matrix and 10 by 10 Hilbert matrix during solving ill- conditioned linear systems. The work has been carried out in FORTRAN on new computational facilities. All calculations have been done in double precision. It is found that, this method is very efficient, fast converging and less time consuming.